PELATIHAN PENGELOLAAN BANK SAMPAH UNTUK MENINGKATKAN PENDAPATAN KELUARGA IBU DAWIS BOUGENVILLE MASARAN SRAGEN - Prastiwi, Putri Intan; Meikhati, Ety meikhati; Wahyuningtyas, Alin Wahyuningtyas; Kristanti, Bernadete Dinar Ayu (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
This community service program aims to enhance the understanding of the Dawis Bougenville community in Masaran, Sragen, regarding effective and sustainable waste bank management. The activities are conducted through socialization, training, and monitoring, employing the Asset-Based Community Development (ABCD) approach to maximize the utilization of local assets. Training includes financial management for the waste bank and practical workshops on crafting from waste materials as an income-generating initiative. The evaluation method applies comparative analysis using the Wilcoxon test to assess program effectiveness by comparing participants' understanding before and after training. Results indicate that participants have comprehensively grasped the material on waste and financial management, along with the skills to transform waste into economic opportunities. The program’s sustainability involves regular monitoring and support for establishing online and offline shops to boost productivity. This initiative is expected to positively impact household economies, foster local entrepreneurship, and support environmental sustainability through efficient waste management practices.